ANALISIS PENERAPAN TARGET COSTING SEBAGAI ALAT PENILAIAN EFISIENSI BIAYA PRODUKSI UNTUK MENINGKATKAN LABA PADA PT. TASINDO CENTRAL PERKASA (TAS KOPER) - Firdaus, Raudatul; Sandari, Tries Ellia (Universitas 17 Agustus 1945 Surabaya, 2018)
ABSTRACTThis study aims to determine the application of methods of analysis of target costing as an assessment tool production cost efficiency to increase profits at the company PT. Tasindo Central Perkasa. PT. Tasindo Cental Perkasa is a company engaged in industrial Bags suitcase in the area waas. To obtain the necessary data, the authors used data collection techniques such as observation, documentation and interview. In this study, the type of data used are primary data. Data obtained from respondents sourced from business owners and employees. From the results of research and analysis show that the company PT. Tasindo Central Perkasa using target costing method in the calculation of cost of production will be more efficient and will earn a profit target of 25% according to the desired company with cost savings can be seen that for the year 2010 amounted to Rp. 3.278.232.000, in 2011 happened savings of Rp. 3.298.160.000, in 2012 happened savings of Rp. 3.329.420.250, 2013 happened savings of Rp. 3.243.068.500, and in 2014 happened savings of Rp. 3.360.151.000.Keyword : target cost, cost, profit